Virš žemės = Above the ground - Kurševa, Maija 1981-; Kurševa, Maija 1981-; Lavrinovičs, Andrejs 1987-; Boer, Bas de 1978-; Broeks, Elfie Pop; Frankl-Slater, Camilla 1993-; Kokkonen, Mika; Strautniekas, Karolis 1988-; Valancauskas, Dziugas; Pavilonis, Martynas 1987-; Dubra, Antanas; Egyboy 1982-; et al. (Popper magazine, 2015)
"Theme of the tenth edition is out of body experiences, intoxication from nature, chemistry, love or heights, psychedelic trips, hallucinations, personal experience and visual side effects." (Verlagsseite)